COLLABORATIVE GOVERNANCE IN EFFORTS TO PREVENT AND CONTROL FOREST AND LAND FIRES IN BATU HAMPAR DISTRICT, ROKAN HILIR DISTRICT - Irlansyah; Muammar Alkadafi (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
The forest and land fire disaster in Batu Hampar District, Rokan Hilir Regency is currently the concern of all parties, each element is trying to work together in collaboration to try to prevent and control forest and land fires, this effort is carried out by involving all parties involved in a partnership, this research uses qualitative methods with a descriptive approach. The key informants in this research were the Regional Disaster Management Agency, PT Sindora Selamat, people who care about fire, and farmers. The results of this research show the collaboration implemented between the Government, the Private Sector, and the Community in preventing and controlling forest and land fires. It has been implemented quite well, but it is still not able to provide significant results in suppressing cases of forest and land fires in Batu Hampar District. This is due to several factors, namely low public awareness in preventing forest fires, extreme weather conditions during the dry season, and lack of facilities and infrastructure. In carrying out collaborations and so on. Until now, Batu Hampar sub-district is still one of the sub-districts with the highest cases of forest and land fires.